Zur Bedeutung der höherwertigen unternehmensorientierten Dienstleistungen für die Entwicklung der Metropolregionen Westdeutschlands - Motzkus, Arnd (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
With the advancing internationalisation of economic relations, high-value, business-orientated services are coming increasingly to represent the economic base for metropolitan regions. In an environment characterised by a division of labour and regional networks of complementary services, the metropolises, as centres performing global functions, exert impulses on the areas around them. At the same time, the integration of service networks within regional partnerships is coming to be a vital prerequisite for regions to compete successfully on the international stage. The dynamic growth of complementary services is currently leading to the emergence of new economic centres in metropolitan regions which are altering the traditional hierarchical relationships between metropolises and their hinterlands, hitherto defined in terms of dependency. A regional planning strategy should address the new types of interaction between functionally specialised locations and centres within the metropolitan regions.
Keywords: Article